SOCIO-DEMOGRAPHIC DEVELOPMENT TRENDS IN KAZAKHSTAN SOCIETY (Based on Public Opinion Polls) - BEYSEMBAEV, Serik (CENTRAL ASIA AND THE CAUCASUS, 2011)
Identifying young people as a separate social group has been practiced since the differences in outlook between the younger and older generations was first noticed. The generation gap, which has existed since the dawn of civilization, has become a target of study for thinkers and scientists; entire fields of research have appeared in philosophy, sociology, and psychology devoted to relations between the generations, whereby particular attention is focused on behavioral traits, as well as on how values are formed among young people as a whole, as well as in their individual groups. Today, there is a wealth of scientific information that allows drawing up a universal portrait of young people as a specific socio-demographic segment of society. The numerous studies show that, along with certain general characteristics (biological and psychological), young people living in different countries of the world differ from each other in many parameters (both external and internal). Despite the growing globalization, it is the local sociocultural environment that continues to have the greatest influence on the younger generation. Demographers customarily classify people between the ages of 15 and 30 as young; however, the social sciences do not stipulate any precise social or age limits to define the concept “young people.” Usually, the question of who to classify as young is determined in each specific case based on the scientific and applied tasks at hand.